2020
DOI: 10.1109/access.2020.2983757
|View full text |Cite
|
Sign up to set email alerts
|

High Step-Up Interleaved Converter Mixed With Magnetic Coupling and Voltage Lift

Abstract: In this paper, a non-isolated high step-up interleaved DC-DC converter for distributed generation applications such as solar cells and fuel cells. The proposed converter mixes the benefits of magnetic coupling, voltage multiplier, and voltage lift techniques to conventional interleaved schemes. The proposed converter's voltage lift technique can increase the voltage gain while guaranteeing low voltage stress of the switches. And the magnetic coupling method can combine the switched capacitor of the voltage mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Several high step‐up two‐phase interleaved dc‐dc topologies can be easily found in the recent literature, but most structures are designed for power levels rated at only a few hundred watts and based on the boost converter. After an extensive search carried out by the authors, only the boost‐type converters reported in Jyotheeswara Reddy and Sudhakar, 30 Nouri et al, 34 and Seo et al 35 were found to achieve a rated power greater than or equal to 1 kW. Overall, it is reasonable to state that the choice of a winning topology should not rely on the voltage gain only, but also on other important characteristics associated with the application.…”
Section: Comparison Among the Proposed Converter And Other Similar To...mentioning
confidence: 99%
“…Several high step‐up two‐phase interleaved dc‐dc topologies can be easily found in the recent literature, but most structures are designed for power levels rated at only a few hundred watts and based on the boost converter. After an extensive search carried out by the authors, only the boost‐type converters reported in Jyotheeswara Reddy and Sudhakar, 30 Nouri et al, 34 and Seo et al 35 were found to achieve a rated power greater than or equal to 1 kW. Overall, it is reasonable to state that the choice of a winning topology should not rely on the voltage gain only, but also on other important characteristics associated with the application.…”
Section: Comparison Among the Proposed Converter And Other Similar To...mentioning
confidence: 99%
“…The voltage-lift methods (VLs) are an effective approach for increasing the output voltage level in high step-up converters. This procedure requires charging a capacitor to a different voltage and then stepping up the output voltage to matching the charged capacitor's voltage level or a multiple-lift circuit employing an n-stage basic diode capacitor VLs circuit was described in [23]- [25] to further rise the VLs. Furthermore, the elimination of magnetic components causes significant current spikes in switching transients.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been presented to tackle the disadvantages of the boost converter such as hard switching, output diode recovery current problem at turn-off, high peak voltage across the switch, and low voltage gain [6]. Switched capacitor, voltage multiplier cells, switched inductor and voltage lift techniques, and magnetic coupling are the major techniques that have been proposed [7][8][9][10][11][12][13]. A hybrid switched inductor converter is used in [14] which does not have a direct connection between the input and output voltage ground and can cause the risk of leakage current in grid-connected PV systems.…”
Section: Introductionmentioning
confidence: 99%